Catalogue of the Byzantine coins in the Dumbarton Oaks Collection and in the Whittemore Collection. Vol. IV : Alexius I to Michael VIII, 1081-1261. Pt. 1 : Alexius I to Alexius V, 1081-1204. - Hendy, Michael F. (Washington)
xi, 443 s.